Commodities, workers, and institutions: analytical and empirical problems in regulation's consumption theory - Mavroudeas, Stavros (2003)
Regulation's theory of consumption has been a significant but rather "hidden" item behind the Fordist/post-Fordist labor process connotations. Its main argument is that working-class consumption was capitalistically commodified only after World War II. Thus, there was no mass consumption to cover the capitalist mass production established in the 1920s. The basis of the post-World War II book was the creation of a social consumption norm (via wages indexation to productivity) that ensured unfettered capitalist accumulation. This schema is both analytically and empirically invalid. - Reproduced.
Keywords: Labour; Consumption